Association of hemoglobin with incidence of in-hospital cardiac arrest in patients with acute coronary syndrome complicated by cardiogenic shock. Issue 9 (September 2019) - Xu, Tiancheng; Liang, Dongjie; Wu, Shengjie; Zhou, Xiaodong; Shi, Ruiyu; Xiang, Wenhao; Zhou, Jian; Wang, Songjie; Shan, Peiren; Huang, Weijian
Objective: This study was performed to investigate the association of the admission hemoglobin level with the incidence of in-hospital cardiac arrest (IHCA) in patients with acute coronary syndrome (ACS) complicated by cardiogenic shock (CS). Methods: In this retrospective study, we reviewed the medical records of consecutive patients with ACS complicated by CS admitted to the coronary care unit from January 2014 to October 2017. Logistic regression models were carried out to evaluate the association between hemoglobin and the incidence of IHCA. Interaction and subgroup analyses were also performed. Results: In total, 211 patients were included in the study, and 61 (28.9%) patients developed IHCA. In the multivariable analysis, hemoglobin was a strong independent predictor of IHCA (odds ratio, 0.971; 95% confidence interval, 0.954–0.989). In the fully adjusted model, patients in the higher hemoglobin tertile were less likely to develop IHCA than patients in the lowest hemoglobin tertile (odds ratio, 0.194; 95% confidence interval, 0.071–0.530). The relationship remained stable in most subgroups except patients aged ≥70 years. Conclusion: In patients with ACS complicated by CS, the incidence of IHCA is related to the hemoglobin concentration, and a high hemoglobin concentration is a protective factor against the development of IHCA.